Computer ontology as an instumental platform to ensure transparency of the European and national qualifications frameworks - S.M. Priyma (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The article analyzed the instrumental platforms of European and national qualifications frameworks. It was found that the European Qualifications Framework contains eight interrelated levels where qualifications determined by training results - triad professional qualities: knowledge, skills and competencies. This approach helps to compare qualifications and simplifies their recognition. The study gives examples of modern instrumentation platforms of the European and national qualifications frameworks to facilitate the establishment of the balance of the qualifications mentioned advantages and disadvantages of each approach. Proved that the qualifications frameworks can successfully functioning based on the ontological approach, the content of which is to present the subject area of knowledge with a help of computer ontologies. Ontology is a description of declarative knowledge in the form of classes with the relation between them. The article highlighted the features editor Protege-OWL for building subject-oriented ontology.